Penerapan Metode Smart Dalam Memilih Ekstrakurikuler Siswa Di SMA Negeri 08 Seluma - Arliyan Arliyan; Sapri Sapri; Rizka Tri Alinse (Jurnal Media Infotama, 2024)
High school 08 Seluma has 7 (seven) extracurricular activities that students can choose, namely male volleyball, female volleyball, male futsal, female futsal, Paskibraka, Pramuka and Tahsin. In helping students to choose the appropriate extracurricular recommendations, there are assessment criteria consisting of 5 criteria, namely interest, talent, experience, parents’ permission and extracurricular achievement. The implementation of SMART Method in choosing extracurricular activities at High school 08 Seluma can help provide extracurricular recommendations for students that are appropriate and in accordance with student assessment criteria, and it can be used as a forum for managing extracurricular activity data at High school 08 Seluma. Based on the tests that have been carried out, the results show that the implementation of SMART method in choosing extracurricular activities at High school 08 Seluma has run well and in accordance with expectations and the application can provide information on the results of recommendations for selecting student extracurricular activities based on the score values that have been given.